A ANALYSIS OF ACIERA F3 AND ACIERA F4 MILLING MACHINE CONDITIONS MEDAN STATE POLYTECHNIC MECHANICAL WORKSHOP - Abdul Rahman; Aulia Salman; Ansharuddin; Bambang Sugiyanto (Politeknik Negeri Medan, 2023)
Abstract Machine tools are the main machines and are indispensable for the engineering industry to produce high-quality machine and equipment components. In the mechanical workshop of the Medan State Polytechnic, apart from being used for student practicum activities, machine tools are also used to produce machine components ordered by several industries and factories around the city of Medan. This study aims to determine the feasibility of the Frais Aciera F3 and F4 machines by examining the main components and measuring their geometric accuracy, whether they still comply with the recommended standards and whether they are still suitable for use. The method used is to measure each component or part that is directly related to its main movements. The result data from the measurement is processed and compared with the reference from the standard. The activity begins with preparing the machine to be tested in static conditions, standard and precise tools, and measuring instruments. The results of the inspection found that the components of the F3 and F4 milling machines were lacking, incomplete, sacked and some components were missing. The accuracy of the machine was still within the permissible standard limits. Key Words: Machine tools, milling machines, conditions, feasibility